Get back in shape! [SMA self-reconfigurable microrobots]. - Yoshida, E.
Self-reconfigurable robotic systems composed of multiple modules have been investigated intensively with respect to their versatility, flexibility, and fault-tolerance. Although some microscale self-assembly systems have been reported, they are passively assembled to predetermined shape by surface tension in an irreversible manner and cannot form arbitrary shapes. To develop a modular microrobot that can actively reconfigure itself, we adopt an actuating mechanism driven by a shape memory alloy (SMA). One of the advantages of an SMA actuator is that it keeps a higher power-weight ratio on microscales than electromagnetic motors.
Keywords: SMA actuator; Fault-tolerance.; Modular microrobot; Power-weight ratio; Self-reconfigurable robotic systems; Shape memory alloy